Silicon phosphide composite material, preparation method thereof, composite negative electrode material, negative electrode sheet and alkali metal ion secondary battery
Patent Information
- Application Number
- CN202611189180.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
硅、磷可与锂、钠、钾等碱金属发生合金化反应,具有较高的理论比容量,但在充放电循环过程中通常伴随明显的体积变化和相结构重构,易造成颗粒破裂、电极结构失稳及界面副反应增加
[0010]根据本发明的实施方案,本发明的磷化硅复相材料以至少两种具有不同硅磷原子比的磷化硅活性相作为主要储能活性组分,通过合金化反应实现较高的可逆比容量,兼具良好的容量释放能力和倍率性能。同时在至少两种具有不同硅磷原子比的磷化硅活性相中构建Fe5PSi相和Fe2PSi相,二者具有不同的铁含量、晶体结构和局域配位环境,并与磷化硅活性相共同构成复相结构。Fe5PSi相和Fe2PSi相协同调控材料内部的局域电子结构和电荷传输特性,促进充放电循环过程中Si-P键等化学键的断裂、重组以及合金化和去合金化循环过程中的相转化,缓解循环过程中相变产生的局部应力集中,提高循环稳定性。综上,本发明在保持较高可逆比容量的同时,改善材料的电化学反应可逆性、倍率性能和循环稳定性,可适配锂离子、钠离子、钾离子等多种碱金属离子二次电池体系。
Smart Images

Figure CN123017925A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery electrode materials technology, and in particular to a silicon phosphide multiphase material and its preparation method, a composite negative electrode material, a negative electrode sheet, and an alkali metal ion secondary battery. Background Technology
[0002] With the rapid development of the new energy industry, alkali metal ion secondary batteries such as lithium-ion and sodium-ion batteries are widely used in electric vehicles, renewable energy storage systems, and portable electronic devices. The specific capacity, electrochemical reaction kinetics, and cycle stability of the negative electrode material are important factors affecting the energy density, power performance, and lifespan of secondary batteries.
[0003] Carbon-based anode materials such as graphite have advantages such as good cycle stability and mature technology, but their theoretical specific capacity is relatively low. Silicon and phosphorus can undergo alloying reactions with alkali metals such as lithium, sodium, and potassium, and have higher theoretical specific capacity, but they are usually accompanied by significant volume changes and phase structure reconstruction during charge-discharge cycles, which can easily lead to particle breakage, electrode structure instability, and increased interfacial side reactions. Summary of the Invention
[0004] In view of this, in order to at least partially solve the aforementioned technical problems, the present invention provides a silicon phosphide multiphase material and its preparation method, a composite negative electrode material, a negative electrode sheet, and an alkali metal ion secondary battery.
[0005] According to one embodiment of the present invention, a silicon phosphide multiphase material is provided, comprising: at least two silicon phosphide active phases with different silicon-phosphorus atomic ratios, and Fe5PSi phase and Fe2PSi phase.
[0006] According to another embodiment of the present invention, a method for preparing the above-mentioned silicon phosphide multiphase material is provided, comprising: adding a phosphorus source to a silicon source in batches and carrying out a chemical reaction under mechanical mixing to obtain a silicon phosphide active phase precursor comprising at least two silicon-phosphorus atomic ratios; adding an iron source to the silicon phosphide active phase precursor in batches and carrying out a chemical reaction under mechanical mixing to obtain a silicon phosphide multiphase material precursor; and subjecting the silicon phosphide multiphase material precursor to a step-heating solid-state reaction heat treatment to obtain the silicon phosphide multiphase material.
[0007] According to another embodiment of the present invention, a composite anode material is provided, comprising a carbon material and the above-mentioned silicon phosphide multiphase material; preferably, the mass ratio of the silicon phosphide multiphase material to the carbon material is (1:1) to (19:1).
[0008] According to another embodiment of the present invention, a negative electrode sheet is provided, comprising a current collector and a negative electrode active layer disposed on the surface of the current collector, the negative electrode active layer comprising the above-mentioned silicon phosphide multiphase material or the above-mentioned composite negative electrode material, a conductive agent and a binder.
[0009] According to another embodiment of the present invention, an alkali metal ion secondary battery is provided, comprising: the above-mentioned negative electrode sheet.
[0010] According to an embodiment of the present invention, the silicon phosphide multiphase material uses at least two silicon phosphide active phases with different silicon-to-phosphorus atomic ratios as the main energy storage active components, achieving a high reversible specific capacity through an alloying reaction, while also possessing good capacity release capability and rate performance. Simultaneously, Fe5PSi and Fe2PSi phases are constructed within the at least two silicon phosphide active phases with different silicon-to-phosphorus atomic ratios. These phases have different iron contents, crystal structures, and local coordination environments, and together with the silicon phosphide active phases, constitute a multiphase structure. The Fe5PSi and Fe2PSi phases synergistically regulate the local electronic structure and charge transport characteristics within the material, promoting the breaking and recombination of Si-P bonds and other chemical bonds during charge-discharge cycles, as well as phase transformations during alloying and dealloying cycles. This alleviates local stress concentration caused by phase transitions during cycling and improves cycle stability. In summary, the present invention maintains a high reversible specific capacity while improving the electrochemical reversibility, rate performance, and cycle stability of the material, making it suitable for various alkali metal ion secondary battery systems such as lithium-ion, sodium-ion, and potassium-ion. Attached Figure Description
[0011] Figure 1 The image shows a scanning electron microscope (SEM) image of the silicon phosphide multiphase material from Example 1.
[0012] Figure 2 Here are the SEM images and elemental distribution diagrams of the silicon phosphide multiphase material from Example 1;
[0013] Figure 3 This is a schematic diagram of the crystal structure of the Fe5PSi phase in the silicon phosphide multiphase material of Example 1;
[0014] Figure 4 This is a schematic diagram of the crystal structure of the Fe2PSi phase in the silicon phosphide multiphase material of Example 1;
[0015] Figure 5 The X-ray diffraction pattern of the silicon phosphide multiphase material in Example 1 is shown below.
[0016] Figure 6 Here is a SEM image of the composite negative electrode material in Example 2;
[0017] Figure 7 The X-ray diffraction pattern of the composite negative electrode material in Example 2 is shown below.
[0018] Figure 8 The charge-discharge curve of the half-cell in Example 3 is shown.
[0019] Figure 9 The rate performance curve of the half-cell in Example 3 is shown.
[0020] Figure 10 The X-ray diffraction pattern of the negative electrode material in Comparative Example 1 is shown.
[0021] Figure 11 The charge-discharge curves are for the half-cell of Comparative Example 1. Detailed Implementation
[0022] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the invention. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the invention for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.
[0023] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.
[0024] When using expressions such as "at least one of A, B and C", they should generally be interpreted in accordance with the meaning that is commonly understood by those skilled in the art (e.g., "a system having at least one of A, B and C" should include, but is not limited to, a system having A alone, a system having B alone, a system having C alone, a system having A and B, a system having A and C, a system having B and C, and / or a system having A, B and C, etc.).
[0025] In this invention, "each independent" means that when there are multiple subjects, they can be the same or different from each other.
[0026] To improve the electrochemical performance of silicon or phosphorus anode materials, related technologies have proposed constructing silicon-phosphorus compounds or silicon-phosphorus composite anode materials. Silicon-phosphorus compounds can comprehensively utilize the energy storage properties of silicon and phosphorus, and their electrochemical reaction performance can be improved by adjusting the silicon-phosphorus ratio, crystallinity, and particle size. Currently, silicon-phosphorus compounds can be prepared using methods such as mechanical ball milling and heat treatment. Simultaneously, these compounds can be composited with carbon materials to enhance electron conductivity and buffer volume changes.
[0027] Related technologies also modify silicon-phosphorus anode materials by constructing structures in which crystalline and amorphous states coexist, introducing metallic or non-metallic elements, and forming multi-component silicon-phosphorus materials. These modifications can improve the conductivity, structural stability, and cycle performance of the materials to a certain extent, but their effects are usually focused on improving the overall electron transport capacity, buffering volume changes, or adjusting the degree of disorder in the materials.
[0028] Currently, iron-silicon-phosphorus anode materials typically employ mechanical ball milling of iron, silicon, phosphorus, and carbon materials. Iron and carbon are used to improve electron transport capacity and structural stability. Furthermore, iron is utilized to promote material structure disorder or the formation of iron-containing components to reduce electrochemical polarization. However, the existence forms and phase compositions of iron-containing components in iron-silicon-phosphorus anode materials are quite complex, and the roles of different iron-containing components in the bulk reaction processes of silicon-phosphorus compounds have not yet been fully distinguished.
[0029] In addition, silicon-phosphorus anode materials still have the following shortcomings: (1) During alloying and dealloying cycles, volume changes and phase structure reconstruction are prone to occur, leading to particle breakage and decreased electrode structure stability; (2) Most silicon-phosphorus compounds have limited intrinsic electron conduction and solid-phase ion migration capabilities, and the reaction process involves the breaking and recombination of chemical bonds such as Si-P bonds, which can easily lead to increased electrochemical polarization and slow phase transformation kinetics under high-rate conditions; (3) Most of them focus on silicon-phosphorus ratio, amorphization treatment, carbon material composite or metal element introduction, but lack targeted regulation of the formation, composition relationship and synergistic effect of different silicon-phosphorus compound phases and metal-containing multi-component phases, making it difficult to take into account high reversible specific capacity, fast reaction kinetics and long-term cycle stability.
[0030] The aforementioned problems limit the further application of silicon-phosphorus anode materials in high-rate, long-cycle, and high-energy-density alkali metal-ion secondary batteries.
[0031] To address these issues, this invention proposes a silicon phosphide multiphase material and its preparation method, a composite anode material, an anode sheet, and an alkali metal ion secondary battery, aiming to solve problems such as insufficient phase composition control, large electrochemical reaction polarization, and insufficient cycle stability in silicon-phosphide anode materials. This invention improves the reversible specific capacity, rate performance, electrochemical reaction reversibility, and cycle stability of the silicon phosphide multiphase material by controlling the compositional relationship between the silicon phosphide active phase with different silicon-phosphide atomic ratios and the Fe5PSi and Fe2PSi phases with different structures. The resulting silicon phosphide multiphase material can be used in alkali metal ion secondary batteries such as lithium-ion, sodium-ion, or potassium-ion batteries.
[0032] Specifically, according to one embodiment of the present invention, a silicon phosphide multiphase material is provided, comprising: at least two silicon phosphide active phases with different silicon-phosphorus atomic ratios, and Fe5PSi phase and Fe2PSi phase.
[0033] According to embodiments of the present invention, the present invention takes the control of the phase composition of silicon phosphide composite material as the technical route, constructs Fe5PSi phase and Fe2PSi phase with different compositions and crystal structures in silicon phosphide active phase systems with different silicon-phosphorus atomic ratios, and obtains silicon phosphide composite material including at least two silicon phosphide active phases, Fe5PSi phase and Fe2PSi phase with different silicon-phosphorus atomic ratios.
[0034] Specifically, in the silicon phosphide multiphase material of the present invention, at least two silicon phosphide active phases with different silicon-to-phosphorus atomic ratios are used as the main energy storage active components, which have different silicon-to-phosphorus bonding environments and alkali metal storage reaction characteristics. Further, Fe5PSi and Fe2PSi phases with different iron contents, crystal structures, and local coordination environments are constructed in the aforementioned silicon phosphide active phases. The Fe5PSi and Fe2PSi phases coexist and together with the silicon phosphide active phase constitute a multiphase structure. Through the synergistic regulation of the silicon phosphide active phase with the Fe5PSi and Fe2PSi phases, the local chemical environment and charge transport characteristics within the material are improved, promoting chemical bond breaking, recombination, and alloying / dealloying phase transformation during charge-discharge cycling, and mitigating structural damage caused by volume changes during cycling. This enables the silicon phosphide multiphase material of the present invention to maintain a high reversible specific capacity while also possessing good rate performance, electrochemical reaction reversibility, and cycle stability.
[0035] In some embodiments, the silicon phosphide active phase includes SiP, SiP2, or silicon-rich Si. m P n Compound phases, m / n > 1. Silicon phosphide active phases with different silicon-to-phosphorus atomic ratios can broaden the capacity range for storing alkali metals, disperse concentrated volumetric strain during charging and discharging of a single active phase, improve the overall reversible specific capacity of the material, and weaken the structural instability caused by drastic volumetric deformation of a single component.
[0036] In some implementations, the Fe5PSi phase is a hexagonal phase with a Ni5As2 structure and space group P63cm. The Fe2PSi phase is a FeP phase with a MnP structure. 1-x Si x Solid solution phase, space group Pnma, 0.4 ≤ x ≤ 0.5. FeP 1-x Si x The solid solution phase is formed by Si partially replacing the P sites in the MnP-structured FeP. The hexagonal Ni5As2-type Fe5PSi phase can construct a continuous conductive network, improving the overall electronic conductivity of the material and reducing electrochemical polarization under high-rate charge-discharge conditions. The MnP-type Fe2PSi phase can disperse the volume stress generated during cycling, improving structural stability. The synergistic coupling of the Fe5PSi and Fe2PSi phases accelerates charge transport, optimizes electrochemical reaction kinetics, and buffers the volume deformation induced by charge-discharge, thereby improving the material's rate performance and cycling stability.
[0037] In some implementations, the mass fraction of iron in the silicon phosphide multiphase material is 5.0% to 24%. This setting facilitates the controllable formation of the Fe5PSi and Fe2PSi phases, thereby constructing a continuous conductive path, dispersing charge-discharge volume stress, optimizing phase transition kinetics, and balancing high reversible specific capacity, excellent rate performance, and long-term cycle stability.
[0038] In some implementations, the particle size of the silicon phosphide multiphase material is 10 nm to 20 μm. This particle size range can shorten the diffusion distance of alkali metal ions, reduce irreversible specific capacity, and buffer volume expansion, thus balancing rate performance, cycle stability, and electrode processability.
[0039] According to another aspect of the present invention, a method for preparing the above-mentioned silicon phosphide multiphase material is provided, comprising: adding a phosphorus source to a silicon source in batches and carrying out a chemical reaction under mechanical mixing to obtain a silicon phosphide active phase precursor comprising at least two silicon-phosphorus atomic ratios; adding an iron source to the silicon phosphide active phase precursor in batches and carrying out a chemical reaction under mechanical mixing to obtain a silicon phosphide multiphase material precursor; and subjecting the silicon phosphide multiphase material precursor to a step-heating solid-state reaction heat treatment to obtain the silicon phosphide multiphase material.
[0040] According to embodiments of the present invention, by adding a phosphorus source to a silicon source in batches and adjusting the local silicon-phosphorus ratio at different reaction stages, an in-situ precursor of silicon phosphide active phases comprising at least two silicon-phosphorus atomic ratios is constructed. By adding an iron source to the silicon phosphide active phase precursor in batches and adjusting the local iron-silicon-phosphorus ratio at different reaction stages, the formation of the Fe2Psi phase reaction components is first promoted, and then a locally iron-rich Fe-Si-P reaction region is constructed, providing a basis for the formation of the Fe5PSi phase. Through a stepped-heating solid-state reaction heat treatment, solid-state diffusion between iron, silicon, and phosphorus is first promoted to stabilize the formation of the Fe2PSi phase, and then the temperature is increased to promote phase reconstruction of the locally iron-rich components, forming the Fe5PSi phase, while retaining at least two silicon phosphide active phases with different silicon-phosphorus atomic ratios.
[0041] In some implementations, batch mixing includes two or more separate processes. Mechanical mixing methods include ball milling. Each addition of the phosphorus source is individually ball-milled at 300–600 rpm for a time of 1–24 h. Similarly, each addition of the iron source is individually ball-milled at 300–600 rpm for a time of 1–12 h. This setup helps to control each stage of the ball milling process, thereby regulating the uniformity of element mixing and the degree of mechanochemical reaction.
[0042] In some implementations, when the addition is done in two batches: the mass ratio of phosphorus source to silicon source in the first addition is (0.8~2):1, and the mass ratio of phosphorus source to silicon source in the second addition is (0.1~1):1. The mass ratio of iron source to silicon source in the first and second additions is independently (0.1~0.3):1. This setting helps to control the local silicon-phosphorus ratio and the local iron-silicon-phosphorus ratio, providing a suitable elemental environment for the formation of the silicon phosphide active phase, Fe2PSi phase, and Fe5PSi phase.
[0043] In some embodiments, the stepped-heat solid-state reaction heat treatment includes a first-stage solid-state reaction heat treatment and a second-stage solid-state reaction heat treatment. The temperature of the first-stage solid-state reaction heat treatment is 550~700℃, the holding time is 1~6h, and the heating rate is 1~10℃·min. -1 The second stage of solid-state reaction heat treatment is carried out at a temperature of 700~900℃, with a holding time of 0.5~3h and a heating rate of 1~10℃·min. -1 This configuration facilitates the synergistic and controllable synthesis of the Fe2PSi phase, Fe5PSi phase, and silicon phosphide active phase, optimizes the multiphase interface structure, and improves charge transport and stress buffering capabilities.
[0044] According to another embodiment of the present invention, a composite anode material is provided, comprising a carbon material and the aforementioned silicon phosphide multiphase material.
[0045] According to embodiments of the present invention, carbon material serves as a conductive and buffering component to improve electron transport performance and mitigate volume changes during charge-discharge cycles. Depending on the electrode conductivity and processing performance requirements, carbon material can be added after the formation of the silicon phosphide multiphase material. Preferably, the carbon material is added after a stepped-heat solid-state reaction heat treatment to reduce its impact on the formation processes of the Fe5PSi and Fe2PSi phases.
[0046] In some implementations, carbon materials and silicon phosphide composite materials can be mechanically combined by ball milling. For example, low-energy premixing (50-200 rpm) and high-energy mechanical compounding (300-600 rpm) can achieve a tight bond between the carbon materials and silicon phosphide composite materials. Low-energy premixing helps to avoid uneven component distribution during the subsequent high-energy mechanical compounding process. High-energy mechanical compounding causes particle refinement and local disordering of the material.
[0047] In some implementations, the mass ratio of silicon phosphide multiphase material to carbon material is (1:1) to (19:1). This setting helps to balance high reversible specific capacity, electronic conductivity, and structural buffering effect, thereby simultaneously improving the overall electrochemical performance.
[0048] In some implementations, the carbon material includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, conductive carbon black, carbon nanotubes, graphene, and carbon fiber.
[0049] According to another aspect of the present invention, a negative electrode sheet is provided, comprising a current collector and a negative electrode active layer disposed on the surface of the current collector, the negative electrode active layer comprising the above-mentioned silicon phosphide multiphase material or the above-mentioned composite negative electrode material, a conductive agent and a binder.
[0050] According to embodiments of the present invention, silicon phosphide multiphase material or composite anode material is used as the active material, and a conductive agent and binder are combined to form an anode active layer, which has high specific capacity, good kinetic characteristics and structural stability, fully utilizes the electrochemical advantages of silicon phosphide multiphase material, and improves the rate performance and cycle life of the anode sheet.
[0051] In some implementations, the conductive agent may be Ketjenblack, the binder may be polyvinylidene fluoride, and the current collector may be copper foil.
[0052] According to another embodiment of the present invention, an alkali metal ion secondary battery is provided, comprising: the above-mentioned negative electrode sheet.
[0053] According to an embodiment of the present invention, by using the above-mentioned negative electrode sheet and relying on the synergistic advantages of the multi-phase material of silicon phosphide, the alkali metal ion secondary battery can have both high discharge specific capacity, good rate performance and stable long cycle characteristics.
[0054] In some implementations, alkali metal ion secondary batteries include lithium-ion batteries, sodium-ion batteries, or potassium-ion batteries.
[0055] In some implementations, alkali metal ion secondary batteries include liquid electrolyte batteries, gel electrolyte batteries, or solid electrolyte batteries.
[0056] The technical solution of the present invention will be further illustrated below through specific embodiments. It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of the present invention is not limited thereto.
[0057] Example 1
[0058] (1) Add phosphorus source in batches
[0059] Under argon protection, 0.647 g of silicon powder and 0.713 g of red phosphorus were weighed and added to a ball mill jar. Grinding balls were added at a ball-to-powder mass ratio of 20:1, the ball mill jar was sealed, and ball milling was carried out at 450 rpm for 8 hours. Subsequently, under argon protection, 0.357 g of red phosphorus was added to the ball mill jar, and ball milling was continued at 450 rpm for another 4 hours to obtain a silicon phosphide active phase precursor containing at least two silicon-to-phosphorus atomic ratios, wherein the total feed amounts of silicon powder and red phosphorus were 0.647 g and 1.070 g, respectively.
[0060] (2) Add iron source in batches
[0061] 0.154 g of iron powder was added to the silicon phosphide active phase precursor obtained in step (1). The ball mill jar was sealed under argon protection and ball milled at 400 rpm for 4 hours to ensure sufficient contact between the iron powder and the silicon phosphide active phase precursor and to induce mechanochemical activation. Subsequently, 0.129 g of iron powder was added, and the ball mill jar was resealed under argon protection. The ball milling was continued at 500 rpm for 4 hours to disperse the added iron powder, thus obtaining the silicon phosphide multiphase material precursor. The total amount of iron powder fed was 0.283 g.
[0062] (3) Step-heating solid-state reaction heat treatment
[0063] The silicon phosphide multiphase material precursor obtained in step (2) is placed in a closed inert atmosphere or vacuum heat treatment device suitable for phosphorus-containing materials and subjected to step-heating solid-phase reaction heat treatment.
[0064] Specifically, first at 3℃·min -1 The temperature was increased to 620℃ at a heating rate and held for 3 hours to promote solid-phase diffusion between iron, silicon, and phosphorus, as well as the formation of the Fe2PSi phase. Subsequently, the temperature was increased at 3℃·min. -1 The temperature was further increased to 800℃ and held for 1 hour to promote phase reconstruction of the local iron-rich components and the formation of the Fe5PSi phase. A shorter high-temperature holding time was used to reduce phosphorus component loss and excessive transformation of the target phase. After the holding time, controlled rapid cooling was performed, followed by cooling to room temperature to obtain a silicon phosphide multiphase material including the Fe5PSi phase, the Fe2PSi phase, and at least two silicon phosphide active phases with different silicon-phosphorus atomic ratios.
[0065] Figure 1 This is a scanning electron microscope (SEM) image of the silicon phosphide multiphase material of Example 1.
[0066] like Figure 1 As shown, silicon phosphide multiphase materials are mainly composed of micron-sized secondary particles formed by the agglomeration of fine primary particles. The particle size ranges from nanometers to micrometers, and the particles exhibit an irregular agglomeration morphology with a relatively rough surface.
[0067] Figure 2The image shows the SEM image and elemental distribution diagram of the silicon phosphide multiphase material of Example 1.
[0068] like Figure 2 As shown, Fe, Si, and P elements are all distributed within the particle region, and no obvious large-scale elemental agglomeration was observed, indicating that the elements are relatively uniformly distributed at the micrometer scale.
[0069] Figure 3 This is a schematic diagram of the crystal structure of the Fe5PSi phase in the silicon phosphide multiphase material of Example 1.
[0070] like Figure 3 As shown, the Fe5PSi phase belongs to the hexagonal crystal system with space group P63cm and cell parameters a=b=6.766Å and c=12.456Å, belonging to the Ni5As2 structure. The Fe5PSi phase, together with the Fe2PSi phase and the silicon phosphide active phase, constitutes a multiphase structure, which is beneficial to improving the electron transport and reaction kinetics of the material.
[0071] Figure 4 This is a schematic diagram of the crystal structure of the Fe2PSi phase in the silicon phosphide multiphase material of Example 1.
[0072] like Figure 4 As shown, the Fe2PSi phase belongs to the orthorhombic crystal system, with space group Pnma and cell parameters a = 5.242 Å, b = 3.059 Å, c = 5.853 Å, and can be represented as FeP 1-x Si x When x approaches 0.5, its nominal composition is represented as Fe2PSi. The Fe2PSi phase, together with the Fe5PSi phase and the silicon phosphide active phase, constitutes a multiphase structure.
[0073] Figure 5 The image shows the X-ray diffraction pattern of the silicon phosphide multiphase material in Example 1.
[0074] like Figure 5 As shown, a comparison of the diffraction peaks of the silicon phosphide multiphase material with the corresponding standard diffraction data reveals that the silicon phosphide multiphase material includes SiP, SiP2, and Si6P. 2.54 The study included silicon phosphide active phases with different silicon-to-phosphorus atomic ratios, as well as Fe5PSi and Fe2PSi phases. This indicates that at least two silicon phosphide active phases with different silicon-to-phosphorus atomic ratios, and Fe5PSi and Fe2PSi phases with different structures, were formed in the silicon phosphide multiphase material. Figure 5 The Si (P2O7) phase is also visible, which may originate from the oxidation of the raw material surface or trace oxygen-containing components introduced during preparation and transfer.
[0075] Example 2
[0076] The silicon phosphide multiphase material from Example 1 was mechanically composited with artificial graphite, and the specific steps are as follows.
[0077] (1) Raw material drying and premixing
[0078] The silicon phosphide multiphase material and artificial graphite from Example 1 were vacuum dried at 80°C for 12 hours to remove surface-adsorbed moisture. 0.800 g of silicon phosphide multiphase material and 0.200 g of artificial graphite were weighed to a mass ratio of 80:20, and then premixed manually for later use.
[0079] (2) Low-energy premixing
[0080] Under argon protection, the pre-mixed silicon phosphide multiphase material and artificial graphite were added to a ball mill jar, with grinding balls added at a mass ratio of 10:1, and the jar was sealed. The mixture was ball-milled at 200 rpm for 2 hours to ensure thorough mixing of the silicon phosphide multiphase material and artificial graphite, yielding a pre-mixed powder.
[0081] (3) High-energy mechanical composite
[0082] The ball mill speed was increased to 450 rpm, and ball milling continued for 6 hours. The ball mill was operated intermittently to reduce the temperature rise caused by continuous mechanical impact. Under high-energy mechanical action, the layered structure of artificial graphite underwent partial peeling, breakage, and defect formation, while the particle size of the silicon phosphide composite material decreased and lattice distortion occurred, forming a tightly contacted composite structure.
[0083] After high-energy ball milling, homogenization was achieved by continuing ball milling at 150 rpm for 1 hour. The powder was then removed under argon protection and vacuum dried at 80°C for 12 hours to obtain the composite anode material.
[0084] Figure 6 This is a SEM image of the composite negative electrode material in Example 2.
[0085] like Figure 6 As shown, after ball milling, the particles exhibit an irregular flaky and fine particle coexisting morphology, with a relatively rough surface.
[0086] Figure 7 The image shows the X-ray diffraction pattern of the composite negative electrode material in Example 2.
[0087] like Figure 7 As shown, the composite anode material exhibits a relatively wide diffuse diffraction background, indicating that the long-range order is reduced after ball milling. However, the (132) crystal plane of SiP, the (200) crystal plane of SiP, the (200) crystal plane of SiP2, the (211) crystal plane of SiP2, and the Si6P crystal plane are still identifiable. 2.54The (304) crystal plane of Si (P2O7), the (200) crystal plane of Fe2PSi, and the (211) crystal plane of Fe2PSi indicate that the composite anode material retains local crystalline characteristics while forming a long-range disordered structure.
[0088] Example 3
[0089] The composite negative electrode material from Example 2 was used as the negative electrode active material and mixed with Ketjen black and polyvinylidene fluoride in a mass ratio of 8:1:1. N-methylpyrrolidone was added and the mixture was stirred thoroughly to obtain a uniform negative electrode slurry. The obtained slurry was coated on the surface of a copper foil current collector, vacuum dried at 60°C for 12 hours, and then punched into negative electrode sheets.
[0090] Using the aforementioned negative electrode as the working electrode, a lithium metal sheet as the counter electrode, and a polypropylene membrane as the separator, a 1 mol / L LiPF6 solution was used as the electrolyte. The electrolyte solvent consisted of ethylene carbonate and diethyl carbonate in a 1:1 volume ratio. A CR2032 coin cell was assembled in an inert atmosphere glove box.
[0091] The assembled half-cell was subjected to constant current charge-discharge testing within a voltage range of 0.001~2.0V. The test results are as follows: Figure 8 As shown.
[0092] Figure 8 The image shows the charge-discharge curves of the half-cell in Example 3, where the specific capacity is expressed as the mass of the composite negative electrode material.
[0093] like Figure 8 As shown, the first-cycle coulombic efficiency of the half-cell in Example 3 is 86.9% at 0.1 A•g -1 The first-cycle reversible specific capacity at the current density is 1442 mAh•g -1 This indicates a high reversible lithium storage capacity.
[0094] Further rate performance tests were conducted on the half-cell of Example 3, with a charge / discharge voltage range of 0.001~2.0V and current densities of 0.1, 0.2, 0.5, 1, 2, 4, 6, 8 and 0.1 A•g, respectively. -1 Cycle 5 times at each current density, and the results are as follows: Figure 9 As shown.
[0095] Figure 9 The graph shows the rate performance of the half-cell in Example 3.
[0096] like Figure 9 As shown, the half-cell of Example 3 at 6 A•g -1 It can still provide approximately 800 mAh•g at current density. -1 The reversible specific capacity, and after being charged and discharged at a high current density, when the current density recovers to 0.1 A•g-1 At that time, its reversible specific capacity can be restored to 1417 mAh•g. -1 This indicates that it has good rate performance and capacity recovery capability. Additionally, at 1 A•g -1 After 100 cycles, the reversible specific capacity is 1180 mAh•g. -1 It exhibits good capacity retention performance.
[0097] Comparative Example 1
[0098] Under argon protection, 0.647 g of silicon powder and 1.070 g of red phosphorus were weighed and added to a stainless steel ball mill jar. Grinding balls were added at a ball-to-powder mass ratio of 20:1. After sealing, a planetary high-energy ball mill was used for the mechanochemical reaction at a speed of 400 rpm for 48 hours, employing intermittent ball milling to reduce the material temperature rise. Under mechanical shearing and impact, silicon and phosphorus underwent a solid-state reaction to obtain iron-free silicon phosphide material that had not undergone heat treatment.
[0099] Under argon protection, 0.800g of the obtained silicon phosphide material and 0.200g of artificial graphite were weighed and added to a ball mill jar. Grinding balls were added at a ball-to-material mass ratio of 10:1. The mixture was first premixed by ball milling at 200 rpm for 2 hours, then mechanically compounded by ball milling at 450 rpm for 6 hours, and finally homogenized by ball milling at 150 rpm for 1 hour. The powder was removed under argon protection and vacuum dried at 80℃ for 12 hours to obtain the negative electrode material.
[0100] Figure 10 The image shows the X-ray diffraction pattern of the negative electrode material in Comparative Example 1.
[0101] like Figure 10 As shown, the material exhibits broadened diffuse diffraction characteristics, and no characteristic diffraction peaks of the Fe5PSi and Fe2PSi phases were observed, indicating that the Fe5PSi and Fe2PSi phases were not formed in the negative electrode material of Comparative Example 1.
[0102] The negative electrode material of Comparative Example 1 was used as the negative electrode active material for the preparation of the negative electrode sheet and the assembly of the coin half-cell. Except for the different negative electrode material, the electrode formulation, slurry preparation method, coating and drying conditions, battery assembly method, and electrochemical testing conditions were all the same as in Example 3. The results are as follows: Figure 11 As shown.
[0103] Figure 11 The charge-discharge curves are for the half-cell of Comparative Example 1.
[0104] like Figure 11 As shown, the first-cycle coulombic efficiency of the half-cell in Comparative Example 1 is 84.7%, at 0.1 A•g -1The first-cycle reversible specific capacity at the current density is 1354 mAh•g -1 After 10 cycles, the reversible specific capacity decreased to 753 mAh•g. -1 The capacity retention rate is only about 55.6%. Furthermore, after 100 cycles, it further decreases to about 10 mAh•g. -1 This indicates that there is a significant irreversible reaction in the system.
[0105] In summary, this invention is advantageous in improving the reversibility and cycling stability of electrochemical reactions while maintaining a high reversible capacity.
[0106] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A silicon phosphide multiphase material, comprising: At least two active silicon phosphide phases with different silicon-to-phosphorus atomic ratios, and Fe5PSi and Fe2PSi phases.
2. The silicon phosphide multiphase material according to claim 1, wherein, The silicon phosphide active phase includes SiP, SiP2, or silicon-rich Si. m P n Compound phase, m / n > 1.
3. The silicon phosphide multiphase material according to claim 1, wherein, The Fe5PSi phase is a hexagonal phase with a Ni5As2 structure. The Fe2PSi phase is of the MnP structure type FeP. 1-x Si x Solid solution phase, 0.4≤x≤0.
5.
4. The silicon phosphide multiphase material according to claim 1, wherein, In the silicon phosphide multiphase material, the mass fraction of iron is 5.0% to 24%. The particle size of the silicon phosphide multiphase material is 10 nm to 20 μm.
5. A method for preparing a silicon phosphide multiphase material as described in any one of claims 1 to 4, comprising: Phosphorus source is added to silicon source in batches, and chemical reaction is carried out under mechanical mixing to obtain silicon phosphide active phase precursors including at least two silicon-phosphorus atomic ratios; Iron source is added to the silicon phosphide active phase precursor in batches, and a chemical reaction is carried out under mechanical mixing to obtain silicon phosphide multiphase material precursor; The silicon phosphide multiphase material precursor was subjected to a step-heating solid-state reaction heat treatment to obtain the silicon phosphide multiphase material.
6. The preparation method according to claim 5, wherein, The batching includes dividing into two or more batches; The mechanical mixing method includes ball milling; Each time the phosphorus source is added, the ball milling speed is independently 300~600 rpm, and the ball milling time is independently 1~24h. The ball milling speed for each addition of the iron source is independently 300~600 rpm, and the ball milling time is independently 1~12 h; and / or, The stepped heating solid-state reaction heat treatment includes a first-stage solid-state reaction heat treatment and a second-stage solid-state reaction heat treatment. The first stage of solid-state reaction heat treatment is carried out at a temperature of 550~700℃, with a holding time of 1~6h and a heating rate of 1~10℃·min. -1 ; The second stage of solid-state reaction heat treatment is carried out at a temperature of 700~900℃, with a holding time of 0.5~3h and a heating rate of 1~10℃·min. -1 .
7. The preparation method according to claim 5 or 6, wherein, In the case where the batch is divided into two parts: The mass ratio of the phosphorus source to the silicon source added for the first time is (0.8~2):1, and the mass ratio of the phosphorus source to the silicon source added for the second time is (0.1~1):1; The mass ratio of the iron source added for the first time and the silicon source added for the second time is independently (0.1~0.3):
1.
8. A composite anode material, comprising a carbon material and a silicon phosphide multiphase material as described in any one of claims 1 to 4; Preferably, the mass ratio of the silicon phosphide multiphase material to the carbon material is (1:1) to (19:1).
9. A negative electrode sheet, comprising a current collector and a negative electrode active layer disposed on the surface of the current collector, wherein the negative electrode active layer comprises a silicon phosphide multiphase material according to any one of claims 1 to 4 or a composite negative electrode material according to claim 8, a conductive agent, and a binder.
10. An alkali metal ion secondary battery, comprising: The negative electrode sheet as described in claim 9.
